Nodular melanoma of the external ear: a rare tumour successfully treated with simple excision - Pająk, Justyna; Lelonek, Edyta; Chlebicka, Iwona; Szepietowski, Jacek (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
External ear melanoma (EEM) is a rare type of melanoma (approximately 1% of all cutaneous melanomas) [1] with higher likelihood of an invasive nature compared to other head and neck melanomas [2]. According to previous data, superficially spreading melanoma is the dominant subtype of the EEM, followed by lentigo maligna and nodular subtype, respectively [1, 3, 4]. Patel et al. [5] discovered that EEM prevalence among young adults is currently higher by 111.9% when compared to former data. Herein, we report a nodular melanoma of the external ear in a middle-aged female, which was successfully removed with simple surgical procedure.